Subsidizing Health-Conscious Behavior Now or Later - Kamila Danilowicz-Gösele; Robert Schwager (Center for Economic Studies and ifo Institute (CESifo), 2016)
In a model where consumers have quasi-hyperbolic preferences, we compare immediate subsidies paid for health-conscious consumption and future subsidies rewarding good health outcome. We characterize the subsidy rates which implement the unbiased choice. These rates differ because of two countervailing effects: (1) the individual applies quasi-hyperbolic discounting to future subsidy receipts, and (2) she can use the future subsidy to partially correct her own future behavior. We further show that future subsidies result in higher costs for a government which discounts exponentially. However, this result does not necessarily hold if the government itself is formed by time-inconsistent individuals.
Keywords: H31; D91; I18; 330; present-bias; quasi-hyperbolic discounting; paternalism; health